Донаукові зацікавлення українським фольклором та етнографією - Кирчів, Р. (Народна творчість та етнографія, 2005)
This material continues the previous publication devoted to pre-scientific interest to Ukrainian Folklore and Ethnography written by R. Kyrchyv (see Number 1, 2005). In this chapter the author is looking at the Ukrainian folklore in Old-Polish folk and written sources. A very detailed analysis was done by an R. Kyrchiv of the early centuries polish poetry (folk and author) and later documents of the 17th Century. The next step which is being done is the search for the folk elements in the Ukrainian literary and historical documents of the 16-17th Centuries. At approximately this time we have also first recordings of Ukrainian Dumas. All of these materials are testifying for the fact that Ukrainian folklore functioned very actively in the 16th and 17th Centuries among various social groups and even influenced writers of different nationalities.